IDENTIFIKASI KEBUTUHAN SISTEM INFORMASI MANAJEMEN PEMANTAUAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN DI KELURAHAN PANTAI JOHOR, KECAMATAN DATUK BANDAR, KOTA TANJUNG BALAI - , Junawan (Universitas Pembangunan Panca Budi, 2019)
The objective of the research was to to identify the development needs of the Management Information System Monitoring the Payment of Land and Building Taxes (PBB) in Datuk Bandar Subdistrict, Tanjung Balai City, and whether the system will increase knowledge, and awareness in paying PBB tax debt in a timely manner. The sampling technique used in this study uses the accidental sampling method with totaling 50 taxpayers. The analytical method uses descriptive analysis and data collection using a questionnaire. The results showed that the collection of PBB still use an inefficient manual system, and the unavailability of a database that updates the PBB taxpayer for payment of land and building tax obligations, so it is necessary to build a Website-Based Information System for Monitoring Land and Building Tax Payments that has database separately in the Datuk Bandar Village Head Office. The majority of PBB taxpayers in Pantai Johor Village agree and strongly agree with the average percentage above 80%, that it is very necessary to build a Management Information System Monitoring the Payment of Land and Building Taxes so that the submission of Land and Building Tax collection is more effective and efficient and timely, so that taxpayer awareness and participation in PBB payments